Pathology for the physical therapist assistant - Goodman, Catherine Cavallaro
No other textbook provides coverage of the essential concepts of disease processes and disorders with the specific needs of the physical therapy assistant in mind. Pathology for the Physical Therapist Assistant provides coverage of disease processes and systemic disorders as well as guidelines, precautions, and contraindications for physical therapy interventions. Catherine Goodman, Kenda Fuller, and Robbie O’Shea share their expertise in a consistent, well-organized approach that defines each disorder, describes the appropriate physical therapy assessment and intervention, and rounds out the discussion with relevant case study examples based on established practice patterns